CRISPR-assisted multi-dimensional regulation for fine-tuning gene expression in Bacillus subtilis. Issue 7 (15th February 2019) - Lu, Zhenghui; Yang, Shihui; Yuan, Xin; Shi, Yunyun; Ouyang, Li; Jiang, Sijing; Yi, Li; Zhang, Guimin
Abstract: Fine-tuning of gene expression is crucial for protein expression and pathway construction, but it still faces formidable challenges due to the hierarchical gene regulation at multiple levels in a context-dependent manner. In this study, we defined the optimal targeting windows for CRISPRa and CRISPRi of the dCas9-α/ω system, and demonstrated that this system could act as a single master regulator to simultaneously activate and repress the expression of different genes by designing position-specific gRNAs. The application scope of dCas9-ω was further expanded by a newly developed CRISPR-assisted O ligonucleotide A nnealing based P romoter S huffling (OAPS) strategy, which could generate a high proportion of functional promoter mutants and facilitate the construction of effective promoter libraries in microorganisms with low transformation efficiency. Combing OAPS and dCas9-ω, the influences of promoter-based transcription, molecular chaperone-assisted protein folding and protease-mediated degradation on the expression of amylase BLA in Bacillus subtilis were systematically evaluated, and a 260-fold enhancement of BLA production was obtained. The success of the OAPS strategy and dCas9-ω for BLA production in this study thus demonstrated that it could serve as a powerful tool kit to regulate the expression of multiple genes multi-directionally and multi-dimensionally in bacteria.